Betwixt ‘Who She Is’ and ‘Who She Is Expected To Be’: Modulating the Perinatal Chaos and Identity Discordance of a Tokophobic Enceinte Being through Narrativised Subjectival Anamnesis of the Matrescent Turmoil - Ms. R. Monisa; Dr. V. David Arputha Raj (The Bioscan, 2024)
It is very likely that in a disturbed individual, who suffers from “Tokophobia” or has undergone “Labour Dystocia,” chaos is experienced from the ante-partum and post-partum vulnerability. It gets compounded, further, by an agencylessness to control physical and mental health, and gets aggravated at an inability to practice naturality and come to terms with normality. Such a disturbing chaos cannot continue and must be overcome through the exercise of some kind of agency which can even be the narratival revisitation of chaos. But then, a disjuncture in the narrativised fabrication of chaos may pave way for an alienation with the existing identity, since narratives and identities are inextricably bound together with one mirroring the other. The panacea for dealing with fragmented narratives can be got through stabilisation techniques of progression from the past to the present and movement from the present into the future. When the narratives, thus, expand upon a comprehensible continuity the sifting identity moves towards a reconfigured one. All these would find a focus in this article, through a close reading of Amber McNaught’s The Anxiety Filled Diary of a Pregnant Hypochondriac: One Ectopic, One Miscarriage, One Last Chance (2019), a memoir on “Tokophobia” and “Labour Dystocia.”